Microbial ecosystems of Shark Bay embayments: assessing their functionality and resilience to potential petroleum contamination - Jiménez de Duarte, Yalimay Mercedes (Curtin University, 2020)
Shark Bay is a protected area which is under risk to be affected by a petroleum spill. An Experimental approach was used to simulate this potential scenario in hypersaline microbial mats from this region. This study has provided new insights and evidence of their biological features that contribute to their ecological resilience and resistance in terms of their microbial composition and functionalities, under short- and long-term petroleum disturbances.